Perancangan Animasi 3D Pylo dan Sofie Mengenalkan Cara Berpikir Rasionalisme - Satria Putra, Nanda; Istiar Wardhana, Mitra; Fefiana Mustikasari, Bunga; Wardani, Nuril Kusuma (JOURNAL OF APPLIED MULTIMEDIA AND NETWORKING, 2024)
The era of Industry 4.0 integrates technology in physical, biological, and digital dimensions, introducing new complexities into our lives. However, the understanding of philosophy, especially rationalism, is often neglected in media. This study aims to design media that are contemporary and to test the media on audiences. To address this, 3D animation was adopted as a means to introduce the concept of rationalism in an engaging and easily understandable manner. The MDLC (Multimedia Development Life Cycle) method was used in developing the animated film "Pylo and Sofie." The film design process went through six stages: concept, design, material collection, production, testing, and distribution. The film, with a duration of 5 minutes and 19 seconds, was uploaded on YouTube and evaluated by 30 viewers via a Google Form questionnaire distributed through WhatsApp and Discord. The film successfully conveyed the concept of rationalism. Positive responses from viewers, with an average score index of 86.29%, rated it as "Highly Suitable" in the evaluation, indicating the film's success in capturing interest and clearly conveying the concept. The evaluation results confirm that "Pylo and Sofie" is effective as an educational tool to enhance public understanding of the concept of rational thinking.